Dental Management of a Patient with Special Health Care Needs - Leopoldo Lucio da Mata; Ana Maria Schroden Rodrigues da Cunha; Andrezza Morais Moronte (Case Reports in Dentistry)
Patients with special health care needs (PSHCN) may have an increased risk of oral disease throughout the course of their life and require particular delivery of dental care due to their medical condition or limitations. The purpose is to report the dental management of a patient with Cornelia de Lange Syndrome (CdLS), which was classified as PSHCN due to physical, behavioural, cognitive, and emotional impairment. A 14-year-old female with a clinical diagnosis of CdLS and its common craniofacial features such as microcephaly, short neck, synophrys, arched eyebrows, downturned angle of the mouth, high arched palate, micrognathia, and microdontia was referred to the hospital where the dental treatment was performed under general anesthesia. Multiple tooth extraction, fillings, and coronary polishing were performed. During the follow-up, we observed that dental restorations were clinically satisfactory and there was an improvement in the patient’s behaviour during dental treatment. Managing and shaping behaviour of such patients are crucial to delivering quality dental care, as they require specialized care due to their behavioural and clinical conditions.